The use of magnetic resonance imaging in the imaging of selected heart diseases - a review of the current literature - Olczyk, Krzysztof; Misiło, Adriana (Journal of Education, Health and Sport, 2023)
Cardiovascular diseases are still the most common cause of death worldwide [1]. Magnetic resonance imaging (MRI) is an advanced diagnostic technique that has become widely used in many fields of medicine, including the diagnosis of heart disease. MRI offers a non-invasive and safe approach to the anatomical and functional assessment of the heart, which enables characterization of the structure and function of this important organ [2]. In this text, we present the current state of knowledge on magnetic resonance imaging in selected heart diseases.